2022
DOI: 10.3389/fonc.2022.831366
|View full text |Cite
|
Sign up to set email alerts
|

Roles of lncRNAs Mediating Wnt/β-Catenin Signaling in HCC

Abstract: Hepatocellular carcinoma (HCC) is considered the second most deadly cancer worldwide. Due to the absence of early diagnostic markers and effective therapeutic approaches, distant metastasis and increasing recurrence rates are major difficulties in the clinical treatment of HCC. Further understanding of its pathogenesis has become an urgent goal in HCC research. Recently, abnormal expression of long noncoding RNAs (lncRNAs) was identified as a vital regulator involved in the initiation and development of HCC. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 176 publications
(189 reference statements)
0
6
0
Order By: Relevance
“…Additionally, FOXD2-AS1 functioned as a molecular sponge of miR-485-5p to control KLK7 transcription, displaying that the FOXD2-AS1/miR-485-5p/KLK7 axis controlled the progression of Papillary thyroid cancer (PTC) [ 21 ]. In addition, FOXD2-AS1 may also activate Wnt/β-catenin signaling pathway؛ This pathway is active in many different types of tumors and plays an important role in controling the growth of cancer cells [ 22 ]. FOXD2-AS1 regulatory mechanisms are very complex and wide, including activation of LSD1 and EZH2, activating Wnt/β-catenin, TRIB3/Akt and NOTCH signaling pathways, inhibition of downstream gene transcription by competitively binding miRNAs and induction of the epithelial to mesenchymal transition (EMT) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, FOXD2-AS1 functioned as a molecular sponge of miR-485-5p to control KLK7 transcription, displaying that the FOXD2-AS1/miR-485-5p/KLK7 axis controlled the progression of Papillary thyroid cancer (PTC) [ 21 ]. In addition, FOXD2-AS1 may also activate Wnt/β-catenin signaling pathway؛ This pathway is active in many different types of tumors and plays an important role in controling the growth of cancer cells [ 22 ]. FOXD2-AS1 regulatory mechanisms are very complex and wide, including activation of LSD1 and EZH2, activating Wnt/β-catenin, TRIB3/Akt and NOTCH signaling pathways, inhibition of downstream gene transcription by competitively binding miRNAs and induction of the epithelial to mesenchymal transition (EMT) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we identified a ceRNA network of hsa_circ_0004535/hsa-miR-1827/CASP8 may have an important regulatory role in T2DM with NAFLD. Studies in a variety of tumors have found that miR-1827 affects patient prognosis by regulating the expression of downstream target genes through binding to their 3'UTRs [35][36][37] . MiR-1827 by targeting PPAR-δ involved in the T2DM disease process 38 .…”
Section: Discussionmentioning
confidence: 99%
“… 94 More information about the role of lncRNAs in mediating WNT/β-catenin in HCC can be found in the review article published recently. 95 …”
Section: Non-coding Rnas Affecting Wnt/β-catenin Signaling In Hccmentioning
confidence: 99%